نبی اکرم صلی اللہ علیہ وسلم اور تشریحاتِ قرآنیہ: ایک تحقیقی و تجزیاتی مطالعہProphet Muhammad (PBUH) and Qur'anic Interpretations: A Research and Analytical Study (Al-Qamar, 2021)
The responsibility of the Holy Prophet PBUH was not only to recognize the Qur'an literally, but also to explain the meanings of the Qur'an. However, there is a difference of opinion among the scholars regarding how much the Prophet has narrated the interpretation of the Qur'an. One group of scholars in which the name of Imam Ibn Taymiyyah is prominent, believes that the Prophet PBUH explained the meaning of the entire Qur'an in the same way as he conveyed the words of the Qur'an. While some scholars such as Imam Suyuti have the opinion that the Holy Prophet PBUH explained the meaning of few verses instead of the entire Qur'an. There are many verses which were not interpreted by the Prophet PBUH, i.e he did not comment on that part of the Qur'an whose interpretation is related to the mere knowledge of the Arabic language. He did not narrate the interpretation of the part whose interpretation is very clear or there is no need for its interpretation. For example, the names of the people of Kahf or color of their dog and species of birds which become alive after death in Hazrat Ibrahim’s story. He did not describe the interpretation of those verses which are related to some matters of the unseen. Such as the reality of the soul or the time of resurrection. On the other hand, It is not justified that the Prophet PBUH explained a few verses. There is a large number of such verses which are not self-explanatory and require explanation and Prophet PBUH explained them. The Prophet's commentary is not only the interpretation of the Qur'an, but other hadiths are actually the interpretation of the Qur'an itself. In fact, most of the fine details of salaah, zakaah, sawm, hajj, inheritance laws, etc. were explained either by the Prophet’s statements or practical demonstrations. It is quite clear that wherever there was a hidden or ambiguous meaning in the words of the Qur'an, the Prophet PBUH explained about it. From this study, it was concluded that the Prophet PBUH neither explained the entire Quran word by word nor only a few verses. It is clear from the books of hadiths that the Prophet PBUH explained the interpretation of most of the Qur'an. The paper aims to analyze that whether the Prophet PBUH narrated the interpretation of the entire Qur'an or only a few verses.
Keywords: ifference of opinion; Interpretation of the Qur'an; Prophet's commentary; Qur'anic Commentaries